2021
DOI: 10.1001/jama.2021.6118
|View full text |Cite|
|
Sign up to set email alerts
|

α2-Adrenergic Agonists or Stimulants for Preschool-Age Children With Attention-Deficit/Hyperactivity Disorder

Abstract: IMPORTANCE Attention-deficit/hyperactivity disorder (ADHD) is diagnosed in approximately 2.4% of preschool-age children. Stimulants are recommended as first-line medication treatment. However, up to 25% of preschool-age children with ADHD are treated with α 2 -adrenergic agonist medications, despite minimal evidence about their efficacy or adverse effects in this age range.OBJECTIVE To determine the frequency of reported improvement in ADHD symptoms and adverse effects associated with α 2 -adrenergic agonists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…11 This near absence of published data is particularly striking given recent large studies (N = 12 639 and N = 955) of preschool-age children with ADHD, disruptive behavior disorders, or both that showed α 2 -adrenergic agonist use has exceeded methylphenidate use in some populations. 10,12 To address this critical gap in the literature and begin constructing an evidence base to guide medication treatment of preschool ADHD, Harstad et al 13 conducted the first study to determine and compare the frequency of reported improvement in ADHD symptoms and adverse effects with α 2 -adrenergic agonist and stimulant medication treatment in this age group. In this retrospective study, electronic health records from 7 outpatient developmental-behavioral pediatrics practices were reviewed for 497 children who were younger than 72 months when they initiated ADHD treatment with an α 2 -adrenergic agonist or stimulant medication.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…11 This near absence of published data is particularly striking given recent large studies (N = 12 639 and N = 955) of preschool-age children with ADHD, disruptive behavior disorders, or both that showed α 2 -adrenergic agonist use has exceeded methylphenidate use in some populations. 10,12 To address this critical gap in the literature and begin constructing an evidence base to guide medication treatment of preschool ADHD, Harstad et al 13 conducted the first study to determine and compare the frequency of reported improvement in ADHD symptoms and adverse effects with α 2 -adrenergic agonist and stimulant medication treatment in this age group. In this retrospective study, electronic health records from 7 outpatient developmental-behavioral pediatrics practices were reviewed for 497 children who were younger than 72 months when they initiated ADHD treatment with an α 2 -adrenergic agonist or stimulant medication.…”
supporting
confidence: 81%
“…Several adverse effects were reported at higher rates for stimulants than α 2 -adrenergic agonists, including moodiness/irritability (50% vs 29%), appetite suppression (38% vs 7%), and sleep difficulties (21% vs 11%), while only the adverse effect of daytime sleepiness was more common with α 2 -adrenergic agonists than stimulants (38% vs 3%). Consistent with prior studies, Harstad et al 13 showed an association between younger age and initiation of α 2 -adrenergic agonists rather than stimulants (age at initiation of treatment × medication class interaction P = .006). Although younger preschool-age children were not more likely to have reported clinical improvement with α 2 -adrenergic agonists than stimulants in this study, children younger than 4 years who were prescribed α 2 -adrenergic agonists were likely to continue receiving those medications longer than those prescribed stimulants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If these are not sufficient, one should consider the beta-blocker propranolol that has good anti-anxiety properties without clouding the mental abilities and has also been reported to improve language in children with ASD [ 297 ]. Alternatively, one may recommend the use of alpha 2-receptor agonists [ 298 ] such as clonidine [ 299 , 300 ] and guanfacine [ 301 , 302 ], usually administered at bedtime especially since clonidine reduces sleep initiation latency and night awakening [ 303 ]. Moreover, caution should be exercised because such adrenergic blocking drugs may cause bradycardia and a drop in blood pressure.…”
Section: Treatment Approachesmentioning
confidence: 99%
“…The Original Investigation titled “α 2 -Adrenergic Agonists or Stimulants for Preschool-Age Children With Attention-Deficit/Hyperactivity Disorder,” published in the May 4, 2021, issue of JAMA , included an error in the Results section that indicated an incorrect number of children who received behavioral therapy before medication initiation. This included indicating that 309, rather than 225, children received behavioral therapy prior to initiation of medication in the Results and Table 1.…”
mentioning
confidence: 99%